(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
At the time when our time is developing hour by hour, it is becoming a very sad situation that we young people cannot speak foreign languages. Our country has its place in the world community, so the development of speaking skills is one of the main problems for us young people to learn a foreign language perfectly and contribute to the development of our country to a certain extent. Therefore, in this article, useful methods for developing the ability to speak a foreign language are mentioned.